2015
DOI: 10.1108/ijqrm-11-2012-0148
|View full text |Cite
|
Sign up to set email alerts
|

Examining determinants of cross buying behaviour in retail banking

Abstract: Purpose – The purpose of this paper is to examine the drivers of the customers’ cross-buying intentions for retail banking services in Hong Kong. Design/methodology/approach – The research model was developed based on literature and tested empirically among 269 customers of retail banks in Hong Kong. Structural equation modelling was used to test the system of relationships. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…The results of hypothesis 1 testing reveal that trust has a positive and significant effect on customer retention. The results of this study are in line with studies conducted by Liu dan Wu (2007), Ratih (2015), Tung and Carlson (2015), which declare that trust has a positive and significant effect on customer retention in the banking industry. This study is contrary to the survey conducted by Luhung and Kusumargiani (2015), which stated that trust has no significant effect on repeat purchases in the Islamic banking industry.…”
Section: Discussionsupporting
confidence: 91%
“…The results of hypothesis 1 testing reveal that trust has a positive and significant effect on customer retention. The results of this study are in line with studies conducted by Liu dan Wu (2007), Ratih (2015), Tung and Carlson (2015), which declare that trust has a positive and significant effect on customer retention in the banking industry. This study is contrary to the survey conducted by Luhung and Kusumargiani (2015), which stated that trust has no significant effect on repeat purchases in the Islamic banking industry.…”
Section: Discussionsupporting
confidence: 91%
“…This is significant since customers offer WoM for a few chosen services and an understanding of WoM antecedents and mediators will benefit marketers (Wien and Olsen, 2012). Therefore, the finding that RCO leads to WoM and PV partially mediates the relationship between RCO and WoM will be a useful finding for the literature on CO. Further, the finding that RCO drives CB and PV partially mediates the relationship is also significant since there is a need to research on the drivers of CB especially in the case of banking services (Tung and Carlson, 2015). The findings suggest that when a customer-oriented firm keeps track of the value it is delivering to customers, it can induce WoM and CB by its customers.…”
Section: Discussionmentioning
confidence: 99%
“…Just a small fraction of these studies (e.g., Hong & Lee, 2012;Soureli et al, 2008) customer expansion and retention model (Kumar et al, 2008). These are the major factors reported in the literature as predictors of cross-buying behavior: perceived convenience, image conflict, commitment, trust, relationship satisfaction, and retention (Tung & Carlson, 2015). Verhoef et al (2002) stated that trust, satisfaction, and value predict cross-buying, whereas Ngobo (2004) reported that image and convenience predict cross-buying.…”
Section: Cross-buying Behaviormentioning
confidence: 99%